HISTORY EDUCATION FOR DISADVANTAGED GROUPS IN THEORY AND IN PRACTICE - Okumus, Osman (International Online Journal of Education and Teaching, 2021)
Many individuals have been considered in disadvantaged group status due to their specific qualities. These individuals’ participation in educational processes requires a special effort. This study is to evaluate history curriculum in theory in terms of disadvantaged groups and to learn history teachers’ opinions about their approaches and experiences towards the disadvantaged groups in practice. The study adopted qualitative research method to meet its purpose and it was designed as case study. Firstly, history curriculum was examined and the statements about disadvantaged groups in the curriculum were explained via descriptive analysis. Then, 11 history teachers were interviewed throughout 2019 with the semi-structured interview form developed by the researcher and the data obtained were analysed via content analysis. It was viewed that indirect emphases about the disadvantaged groups were included in history curriculum and history teachers were given the responsibility for the inclusion of students with different qualities in learning processes. It was determined in the interviews carried out with teachers that teachers had limited knowledge about the disadvantaged group and the individuals included in the group, they understood multi-cultural individuals and disabled individuals from the concept, communication was the biggest problem experienced with the disadvantaged students, and teachers carried out mostly student-centred activities in order to overcome such obstacles.